A naturally derived dextran–peptide vector for microRNA antagomir delivery. Issue 35 (23rd March 2015) - Tang, Qiong; Lei, Xia; Cao, Bin; Sun, Bingbing; Zhang, Yanqiao; Cheng, Gang
Abstract : A dextran–peptide hybrid, Dex10-R5H5(40%), was developed to deliver microRNAs. Antagomir-149s delivered by Dex10-R5H5(40%) were efficiently internalized by cells and escaped from endosomes. Antagomir-149 reduced the level of miRNA-149 by 76%. Abstract : Single stranded microRNAs and their antagomirs are unstable and polyanionic, which impedes efficient cellular uptake and reduces half-life. Therefore, effective delivery systems with low toxicity for microRNAs are urgently needed for the success of microRNA-based therapy. Here, a dextran–peptide hybrid, Dex10-R5H5(40%), was developed as a carrier to deliver microRNAs. Dex10-R5H5(40%) loaded with antagomir-149 could reduce the level of endogenous microRNA-149 by 76% and it is more effective than the commercially available transfection reagent, RNAiMAX, which leads to 67% reduction. Additionally, Dex10-R5H5(40%) exhibited no cytotoxicity to HepG2 cells. These results indicate that the dextran–peptide hybrid may be a promising delivery system for the safe and efficient microRNA-based therapy.